Cellule staminali mesenchimali associate a core-decompression nel trattamento delle necrosi cefaliche - Capuano, N.; Carbone, F.; Grillo, G.; D’Addona, A. (Lo Scalpello - Journal, 2019)
MESENCHYMAL STEM CELLS ASSOCIATED TO CORE DECOMPRESSION IN THE TREATMENT OF OSTEONECROSIS OF THE FEMORAL HEAD Osteonecrosis of the femoral head often affects young active adults and leads to destruction of the hip joint and severe arthritis. Various head-preserving procedures have been used to avert or delay the need for total hip arthroplasty. Non vascularised bone grafting with core decompression is our preferred technique to treat surgically patients with pre-collapse ONFH. In this study we present a clinical case treated with Osteoplant flex scaffold (equinus bone graft) with mesenchymal stem cells.